Development of a dissolution test method for enrofloxacin tablets using factorial design. (1st January 2013) - Issa, Michele Georges; Duque, Marcelo Dutra; de Queiros, Aline Rotildes; Françoso, Juliana Buono; Ferraz, Humberto Gomes; Rodrigues, Leticia Norma Carpentieri
Dissolution testing has emerged in the pharmaceutical field as a very important tool to characterise the performance of drug products. Enrofloxacin is an antimicrobial frequently used in veterinary medicine that has no dissolution method described in pharmacopoeias. In vitro dissolution tests of enrofloxacin tablets were performed using different test parameters under 'sink' conditions. A two-factor three-level factorial design was obtained using statistical software, on which nine runs were performed. The independent variables were rotation speed (50, 75 or 100 rpm) and dissolution medium (HCl 0.01 M, purified water or phosphate buffer pH 6.8). The response evaluated (dependent variable) was dissolution efficiency (%). The method using hydrochloric acid 0.01 M as the dissolution medium in USP Apparatus 2, with a rotation speed of 75 rpm proved to be the most appropriate. Under these conditions, this method was capable of distinguishing between different tablet formulations containing enrofloxacin.